Feature Analysis: A Method for Analyzing the Role of Ideology in App Design - Hasinoff, Amy A.; Bivens, Rena (Journal of digital social research, 2021)
Many apps are designed to solve a problem or accomplish a task, such as managing a health condition, creating a to-do-list, or finding work. The solutions that app developers offer reflects how they believe that users and other stakeholders understand the problem. Each individual developer may have different ideas but analyzing many apps together can reveal the average or typical ways that developers in the set think about the problems that their apps are designed to solve. Building on content analysis, interface analysis, the concept of affordances, and speculative design, this article offers a new method that we call “feature analysis” to analyze what a set of apps designed to solve the same problem can tell us about the relationship between app design and ideology. By counting and classifying the features in a set of apps, feature analysis enables researchers to systematically answer questions about how app developers’ design choices reflect existing cultural norms, assumptions, and ideologies.